2022
DOI: 10.3390/agronomy12020512
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity and Plant Defence Induction by Cinnamomum cassia Essential Oil Application on Malus domestica Tree: A Molecular Approach

Abstract: Essential oils (EOs) are actively investigated as an alternative to numerous synthetic biocide products. Due to their large spectra of biological activities, the impact of EOs on non-target organisms should be characterized for biopesticide development purposes. In this study the potential phytotoxicity of Cinnamomum cassia EO (CEO) on apple trees (Malus domestica) were investigated in terms of oxidative burst (glutathione redox state) and damage (malondialdehyde). At 2%, CEO concentration the reduced glutathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…These compounds could be the cause of the behavioral change we recorded here, as several studies have shown their repulsive or toxic effect on several aphid species (Bruce et al 2005, Abbassy et al 2009). Beside this suggested impact on volatiles metabolites, an experiment regarding plant defense elicitation using qRT-PCR on major apple defense pathways highlighted an increased gene expression following cinnamon essential oil application similar to SAR-inducer Bion 50 WG (SYNGENTA, active substance Acibenzolar-S-methyl) (Werrie et al 2022). Moreover, prolonged induction of genes from pathogenesis-related proteins, parietal modification, and phenylpropanoids pathway was observed.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds could be the cause of the behavioral change we recorded here, as several studies have shown their repulsive or toxic effect on several aphid species (Bruce et al 2005, Abbassy et al 2009). Beside this suggested impact on volatiles metabolites, an experiment regarding plant defense elicitation using qRT-PCR on major apple defense pathways highlighted an increased gene expression following cinnamon essential oil application similar to SAR-inducer Bion 50 WG (SYNGENTA, active substance Acibenzolar-S-methyl) (Werrie et al 2022). Moreover, prolonged induction of genes from pathogenesis-related proteins, parietal modification, and phenylpropanoids pathway was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The work [ 63 ] reported on the phytotoxic effect of CCEO in the treatment of apple leaves. Moreover, CCEO has elicitor activity in plants against phytopathogens [ 68 , 69 ]. From the component composition of essential oils, it is known that monoterpenes, in particular 1,8-cineole and carvone, have the greatest phytotoxic effect [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that EOs could be used to control many crop pests by being sprayed on plants to develop the natural defence system [82][83][84][85]. As documented by Werrie et al [86] following EO application, complex modifications of oxidative stress-related metabolites occur in plants (e.g., increases in expression levels of specific genes belonging to PR proteins, hormonal signalling, phenylpropanoids and parietal modification pathways). As demonstrated, the plant defence induction occurring below the phytotoxicity threshold is significantly important for EO application in horticulture.…”
Section: Phytotoxic Effect Of Essential Oilsmentioning
confidence: 99%